Novel UGT1A1 Gene Mutations in a Boy with Crigler–Najjar Syndrome Type II - Pérez-Solís, David; Montes-Zapico, Bárbara; Rodríguez-Dehli, Ana-Cristina; García-Hoyos, María; Arroyo-Hernández, Mireia (Journal of Pediatric Genetics, 2020)
In this article, we reported a patient with Crigler–Najjar syndrome type II with high-unconjugated bilirubin levels that decreased after phenobarbital treatment. The patient had two novel missense mutations in the UGT1A1 gene and a promoter variant in one allele. One mutation was c.1001T > C, that predicted leucine to proline substitution at position 334 (p.Leu334Pro). The other, c.1139A > G, predicted glutamic acid to glycine replacement at position 380 (p.Glu380Gly). In silico analysis indicated that both mutations are likely pathogenic.
Keywords: Crigler–Najjar syndrome; hyperbilirubinemia; hereditary; genetic variation